Advancements in Cytomegalovirus Management Among Solid Organ Transplant Recipients: Insights From the ESOT CMV Workshop 2023 - Luca Toti; Nassim Kamar; Sophie Alain; Sophie Alain; Oriol Manuel; Nikolina Basic-Jukic; Paolo Antonio Grossi; Hannah Kaminski; Paolo Solidoro; Luciano Potena (Transplant International)
Cytomegalovirus (CMV) infection poses significant challenges in solid organ transplant (SOT) recipients, impacting graft outcomes, morbidity, and in some cases survival. The ESOT CMV Workshop 2023 convened European experts to discuss current practices and advances in the management of CMV with the aim of improving the quality of life of transplant recipients. Discussions covered crucial areas such as preventive strategies, diagnostic challenges, therapeutic approaches, and the role of cell-mediated immunity (CMI) monitoring. Despite advances, ambiguity persists in optimal CMV management across European transplant centers. Preventive strategies, including universal prophylaxis and pre-emptive therapy, are effective but consensus is lacking with respect to the preferred approach. Diagnostic challenges such as standardization of viral load thresholds and detection of end-organ disease complicate timely intervention. While newer therapies like maribavir hold promise for treating complicated CMV infections, sustaining viral clearance remains a challenge. Integrating CMI monitoring into CMV management could personalize treatment decisions but has limitations in in terms of predictive value and accessibility. Further research is needed to fill these gaps and optimize CMV management. The collaborative efforts, led by the European Society for Organ Transplantation (ESOT), aim to standardize and improve CMV care, ensuring better outcomes for SOT recipients.